Investigative study on common curing methods in reducing plastic shrinkage in concrete slabs - Nurul Nadiah , Zulkefle (2012)
Concrete hydration process is an action between the mixing of cement and water. The process produces heat release which can turn into a harmful reaction if the rate of heat released is higher than the concrete bleeding. The heat released will lead to shrinkage which every single concrete structure will be experiencing. The initial concrete shrinkage occurred can be classified as plastic shrinkage which is the most vital shrinkage that needs to be preserved. The main objective of this study is to investigate the methods to control shrinkage in concrete slabs using common curing techniques used in the construction industries. This study focused on using different curing methods on concrete slabs. Five different slabs were used as the testing samples for three common curing techniques; air dry, wet burlap she and water spray curing. For wet burlap sheeting and water spraying techniques, two types of curing durations had been applied; one day and three days of curing had been practiced. All of the slabs were stored and tested at an open space which considers being the same environment in the construction. The test involved using mechanical strain gauge that indicated shrinkage readings through the movement of locating discs placed on the slabs. The testing of each of the slabs has been done after one day of concrete setting and continued tested until the fourth day after the concrete was set. The results and observations showed even though air dry curing method did not involve moisture contact other than the mixing water, the overall analysis showed that it was a better curing technique than using wet burlap sheeting. Water spray curing technique generated the most effective curing technique among other curing techniques used in this study.